Effectiveness and adverse effects of immersive technologies used for rehabilitation of patients with non-specific neck pain: a systematic review - Joanna S. Kostka; Agnieszka Zawadzka-Fabijan; Dariusz Działa; Bogumiła Bruc; Magdalena Pruszyńska; Gabriela Figas; Rory J. O'Connor; Antti Malmivaara; Jolanta E. Kujawa (Journal of Rehabilitation Medicine)
Objective: The aim of this study is to evaluate the effectiveness of immersive technologies in the rehabilitation of patients with non-specific neck pain and identify any potential side effects associated with their use.